PERBANDINGAN ATURAN HUKUM ANTARA INDONESIA DENGAN AMERIKA SERIKAT MENGENAI PLAGIARISME KARYA CIPTA LAGU - Rayhan Atthallah Malik Agustiar, (2023)
Plagiarism of copyrighted songs is a form of copyright infringement in the form of taking or plagiarizing either parts or an entire song created by another person and then publish the plagiarized song product and recognizing it as the property of the perpetrator himself. It also known that plagiarism of copyrighted songs is one of the most common forms of copyright infringement. Based on this explanation, the author examines the indicators of plagiarism of copyrighted songs and the forms of remedies based on law comparisons between Indonesia and the United States. This research was carried out in a normative juridical manner, namely through the study of legal aspects in writing, which underlies the method of collecting data through the method of literature. The theoretical review used in this study is the theory of comparative law, legal protection and responsibility. The result of this study is that the fact that both in Indonesia and the United States, victims of plagiarism of copyrighted songs can file a lawsuit to obtain compensation from the perpetrator, but in the United States plagiarism is basically not considered a violation of law but is still a violation morally. The two countries also both emphasized the existence of remedies for perpetrators of copyrighted songs plagiarism, but the nominal calculation of remedies for copyright infringement is not explained in the Indonesian Copyright Law but is explained in detail in Title 17 of the U.S. United States Code. Keywords: Comparison, Indicator, Plagiarism, Copyrighted Songs, Remedies.